Remote tutoring: an effective strategy to improve programming education in engineering - Duarte, Riam Ferreira Lopes; Longhini, Tatielle Menolli; Toledo, Buno de Souza (Brazilian Journal of Production Engineering, 2025)
The subjects of Programming Logic and Computer Programming have historically shown high failure and dropout rates. Tutoring programs, already established in various areas and for different audiences, have proven effective as a teaching support strategy. This research found that 70% of students who enrolled in these subjects failed at least once, taking on average one to three semesters to pass. Based on the analysis of student profiles, a tutoring program was developed with sessions tailored to their needs, aiming to consolidate fundamental knowledge and improve performance in programming courses within the Engineering programs in Production, Civil, and Environmental and Sanitary Engineering at IFMG Governador Valadares campus. This project is expected to enhance the learning process and reduce high rates of failure, dropout, and abandonment.